Black carbon deposited in Hariqin Glacier of the Central Tibetan Plateau record changes in the emission from Eurasia. (15th March 2021) - Wang, Mo; Xu, Baiqing; Wang, Hailong; Zhang, Rudong; Yang, Yang; Gao, Shaopeng; Tang, Xiangxiang; Wang, Ninglian
Abstract: Black carbon (BC), by the combustion of fossil fuels and biomass, has profound effects on climate change and glacier retreat in industrial eras. In the present study, we report refractory BC (rBC) in an ice core spanning 1850–2014, retrieved from the Hariqin Glacier of the Tanggula Mountains in the central Tibetan Plateau, measured using a single particle soot photometer (SP2). The rBC concentration shows a three-fold increase since the 1950s. The mean rBC concentration was 0.71 ± 0.52 ng mL −1 during 1850s–1940s and 2.11 ± 1.60 ng mL −1 during 1950s–2010s. The substantial increase in rBC since the 1950s is consistent with rBC ice core records from the Tibetan Plateau and Eastern Europe. According to the predominant atmospheric circulation patterns over the glacier and timing of changes in regional emissions, the post-1950 amplification of rBC concentration in the central Tibetan Plateau most likely reflects increases in emissions in Eastern Europe, former USSR, the Middle East, and South Asia. Despite the low-level background rBC concentrations in the ice cores from the Tibetan Plateau, the present study highlights a remarkable increase in anthropogenic BC emissions in recent decades and the consequent influence on glaciers in the Tibetan Plateau. Graphical abstract: Image 1 Highlights: BC deposition (1850–2014) in a Central Tibetan glacier has tripled since the 1950s. BC emission from Indian monsoon domain mainly contributes to the increase. BC deposition in Tibetan glaciers is at the lowest level in Northern Hemisphere.